A Antropização das paisagens alentejanas na Pré-história Recente e Proto-história: entre o selvagem e o antrópico - RIBEIRO, Inês (2022)
The Alentejo region is the largest region of the country bordered to the north by the river Tagus, to the south by the Algarve region, to the east by Spain and to the west by the Atlantic Ocean. It is therefore a vast area which currently presents different concentrations of population and, in geomorphologic terms, quite diversified. This natural space was, between the 5th and 1st millennium BC, lived and perceived in different ways by these ancient populations who, depending on their own constraints and/or social preferences, occupied it in different ways, favouring, in some phases, lower plateaus and, in others, higher ones. In this work we try to understand and to map this evolutionary dynamic and its relation between the anthropic and the natural, trying to perceive preferential spaces according to chronologies.